Letter to Jane Tolmach from Stanley Mosk - Stanley Mosk:::::: (1962)
A letter to Jane Tolmach from Stanley Mosk, California Attorney General. The letter thanks Jane for sending him newspaper clippings from the Oxnard paper regarding right wing extremism.